Testing complete and compact radial basis functions for solution of eigenvalue problems using the boundary element method with direct integration. Issue 2 (4th March 2018) - Loeffler, Carlos; Frossard, Abraão; Lara, Luciano
ABSTRACT: This paper analyses the performance of the main radial basis functions in the formulation of the Boundary Element Method (DIBEM). This is an alternative for solving problems modeled by non-adjoint differential operators, since it transforms domain integrals in boundary integrals using radial basis functions. The solution of eigenvalue problem was chosen to performance evaluation. Natural frequencies are calculated numerically using several radial functions and their accuracy is evaluated by comparison with the available analytical solutions and with the Finite Element Method as well. The standard radial basis functions have presented similar performance to compact radial functions, being even slightly superior.